Sea ice increases benthic community heterogeneity in a seagrass landscape. (30th September 2020) - Pascal, Ludovic; Bernatchez, Pascal; Chaillou, Gwénaëlle; Nozais, Christian; Lapointe Saint-Pierre, Mathilde; Archambault, Philippe
Abstract: Sea ice plays an important role in subpolar seagrass meadows. It protects meadows against wave action and extreme temperatures. On the other hand, sea ice destroys seagrass leaves and removes plots of sediments and organics debris, leaving long-lasting ice-made tidal pools of various shapes and sizes within the meadow. The present study aimed at investigating the effect of sea ice on benthic community structure and biogeochemical processes in a subpolar seagrass meadow. Vegetated areas (V), artificially-created (aTP), and natural (nTP) tidal pools were sampled from April to October 2018 in a seagrass meadow located at Manicouagan Peninsula (Québec; 49°5′36″N, 68°12′44″W). aTP and nTP showed similar sediment characteristics with coarser sediment and lower particulate organic carbon and total nitrogen content but also lower NOx and higher NH4 + and PO4 3− porewater concentrations as compared to V. Benthic macrofauna communities showed a strong seasonality with very reduced total density, biomass and species richness during wintertime (from December to April) relatively to summertime (from June to September). Benthic macrofauna communities were also more diversified and abundant in V than in aTP and nTP. Species assemblages in aTP and nTP represented a subset of species assemblages in V with any species found exclusively in tidal pools. However, total biomass was similar among treatments, suggesting that tidal pools sheltered larger individuals than vegetated areas. These results underline the importance of considering the spatial heterogeneity of seagrass meadows when assessing the functioning of these ecosystems. Graphical abstract: Image 1 Highlights: Sea ice influences heterogeneity of subpolar seagrass meadow in space and time. The ice cover reduces macrofauna abundance, biomass and richness during wintertime. Sea ice allows the formation of long-lasting ice-made tidal pools within the meadow. Formation of tidal pools did not affect β- and γ-diversity at the landscape scale. Formation of tidal pools enlarge the size spectrum of species colonizing them.